K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 12 2017

a) \(\frac{2x-4y}{0,2x^2-0,8y^2}\) = \(\frac{2(x-2y)}{0,2(x^2-4y^2)}\) = \(\frac{2(x-2y)}{0,2(x-2y)(x+2y)}\)

= \(\frac{10}{x+2y}\) = \(\frac{10}{5}\) = 2 Vì \(x+2y=5\)

1 tháng 12 2017

b) Ta có : \(\frac{x^2-9y^2}{1,5x+4,5y}\) ĐKXĐ : \(x\ne -3y\)

Ta có : \(3x-9y=1 \) => \(x-3y = \frac{1}{3}\) => x= \(\frac{1}{3} + 3y\) ( Thỏa mãn ĐKXĐ )

Ta có : \(\frac{x^2-9y^2}{1,5x+4,5y}\) = \(\frac{(x-3y)(x+3y)}{1,5(x+3y)}\) = \(\frac{x-3y}{1,5}\) = \(\frac{\frac{1}{3}}{1,5}\) = \(\frac{2}{9}\)

a: \(A=\dfrac{10ab^2-5a^2}{16b^2-8ab}=\dfrac{5a\left(2b^2-a\right)}{8b\left(2b-a\right)}=\dfrac{\dfrac{5}{6}\cdot\left(2\cdot\dfrac{1}{49}-\dfrac{1}{6}\right)}{\dfrac{8}{7}\cdot\left(\dfrac{2}{7}-\dfrac{1}{6}\right)}=-\dfrac{37}{48}\)

b: \(A=\dfrac{a^7+1}{a^8\left(a^7+1\right)}=\dfrac{1}{a^8}=\dfrac{1}{0.1^8}=10^8\)

c: \(=\dfrac{2\left(x-2y\right)}{0.2\left(x^2-4y^2\right)}=\dfrac{10}{x+2y}=\dfrac{10}{5}=2\)

d: \(=\dfrac{\left(x-3y\right)\left(x+3y\right)}{1.5\left(x+3y\right)}=\dfrac{x-3y}{1.5}=\dfrac{3}{1.5}=2\)

27 tháng 7 2017

\(P=27y^3+9y^2+y+\dfrac{1}{27}=\left(3y+3\right)^3\)

Với \(y=\dfrac{2}{3}\) ta có:

\(P=\left(3.\dfrac{2}{3}+3\right)^3=5^3=125\)

\(Q=x^2+4y^2-2x+10+4xy-4y\)

\(=\left(x^2-2x+4xy\right)+4y^2-4y+10\)

\(=\left[x^2-2x\left(1-2y\right)+\left(1-2y\right)^2\right]+4y^2-4y+10-\left(1-2y\right)^2\)\(=\left(x+2y-1\right)^2+4y^2-4y+10-1+4y-4y^2\)\(=\left(x+2y-1\right)^2+9\)

Với \(x+2y=5\) , ta có:

\(Q=\left(5-1\right)^2+9=25\)

18 tháng 7 2016

(x²+4xy+4y²)-(2x+4y)+10=(x+2y)²-2(x+2y)+10=5²-10+10=25 :333

18 tháng 7 2016

:333 là biểu cảm nhé

18 tháng 8 2020

cảm ơn bạn nha

a) Ta có: 10(x-y)-8y(y-x)

\(=10\left(x-y\right)+8y\left(x-y\right)\)

\(=2\left(x-y\right)\left(5+4y\right)\)

d) Ta có: \(x^2y-x^3-9y+9x\)

\(=x^2\left(y-x\right)-9\left(y-x\right)\)

\(=\left(y-x\right)\left(x^2-9\right)\)

\(=\left(y-x\right)\left(x-3\right)\left(x+3\right)\)

e) Ta có: \(2x+2y-x^2-xy\)

\(=2\left(x+y\right)-x\left(x+y\right)\)

\(=\left(x+y\right)\left(2-x\right)\)

f) Ta có: \(x^2-25+y^2+2xy\)

\(=\left(x+y\right)^2-5^2\)

\(=\left(x+y-5\right)\left(x+y+5\right)\)

g) Ta có: \(x^2-2x-4y^2-4y\)

\(=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)\)

\(=\left(x+2y\right)\left(x-2y-2\right)\)

h) Ta có: \(x^2\left(x-1\right)+16\left(1-x\right)\)

\(=x^2\left(x-1\right)-16\left(x-1\right)\)

\(=\left(x-1\right)\left(x^2-16\right)\)

\(=\left(x-1\right)\left(x-4\right)\left(x+4\right)\)

Bài 4: 

a: \(\Leftrightarrow x^3-3x^2+3x-1-x^3-27+3x^2-12=2\)

\(\Leftrightarrow3x-40=2\)

=>3x=42

hay x=14

b: \(\Leftrightarrow x^3+8-x^3-2x=0\)

=>-2x+8=0

=>-2x=-8

hay x=4

c: \(x\left(x-2\right)+\left(x-2\right)=0\)

=>(x-2)(x+1)=0

=>x=2 hoặc x=-1

d: \(5x\left(x-3\right)-x+3=0\)

=>5x(x-3)-(x-3)=0

=>(x-3)(5x-1)=0

=>x=3 hoặc x=1/5

e: \(3x\left(x-5\right)-\left(x-1\right)\left(3x+2\right)=30\)

\(\Leftrightarrow3x^2-15x-3x^2-2x+3x+2=30\)

=>-14x=28

hay x=-2

f: \(\Leftrightarrow\left(x+2\right)\left(x+30-x-5\right)=0\)

=>x+2=0

hay x=-2